Ressources Alimentaires De Eidolon helvum (Kerr, 1792), Espece Proche De La Menace (Abidjan, Côte d’Ivoire) - Niamien Coffi Jean Magloire; Kadjo Blaise; Koné Kéassemon Cédessia Hervé; N’Goran Kouakou Eliézer (European Scientific Journal, ESJ, 2017)
Food resources of the straw-colored fruit bats Eidolon helvum (Kerr, 1792), a near-threaned species in Abidjan-Plateau were studied from August 2007 to July 2008. Faeces collection under sleeping trees and direct observations were made in order to access qualitative composition and temporal distribution of food resources of Eidolon helvum. Results show that 16 species of plants grouped into eight families and classified in three categories of plant organs were exploited by these bats. Among them, three species of plants appeared for the first time in the diet of the frugivorous bats in Côte d’Ivoire. Fruit food resources were most abundant (83%) and fruits of Ficus genus were dominant (45%). The distribution of food resources varied with the season.